2012
DOI: 10.1007/s10753-012-9560-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll-like Receptor 3 Polymorphisms with Chronic Hepatitis B and Hepatitis B-Related Acute-on-Chronic Liver Failure

Abstract: Hepatitis B virus (HBV) infection is one of the major causes of chronic liver inflammation. Toll-like receptor 3 (TLR3) plays a key role in innate immunity and is responsible for recognizing viral pathogens. It has been reported that the TLR3 C1234T polymorphism is associated with various diseases. The aim of this study was to investigate whether TLR3 polymorphisms were correlated with susceptibility to chronic HBV infection. Two polymorphisms in the TLR3 gene, A952T and C1234T, were tested by direct sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
1
30
2
Order By: Relevance
“…Genetic variations in TLR3 have been correlated with susceptibility to various diseases, including CHB and HCC. Previous studies reported that the TLR3 C1234T polymorphism was associated with increased susceptibility to CHB (Rong et al, 2013), as well as HCC (Li and Zheng, 2013). The present study demonstrated that the TLR3 rs3775290 polymorphism was associated with a decreased risk for CHB, HBV-related LC, and HCC.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Genetic variations in TLR3 have been correlated with susceptibility to various diseases, including CHB and HCC. Previous studies reported that the TLR3 C1234T polymorphism was associated with increased susceptibility to CHB (Rong et al, 2013), as well as HCC (Li and Zheng, 2013). The present study demonstrated that the TLR3 rs3775290 polymorphism was associated with a decreased risk for CHB, HBV-related LC, and HCC.…”
Section: Discussionsupporting
confidence: 71%
“…Genetic variations in TLR3 have been correlated with susceptibility to various diseases, including viral hepatitis and HCC (He et al, 2007;Ishizaki et al, 2008;Etem et al, 2011;Al-Qahtani et al, 2012;Sironi et al, 2012;Lee et al, 2013;Li and Zheng, 2013;Rong et al, 2013). However, little is known concerning TLR3 gene polymorphisms and HBVrelated CHB, LC, and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…TLR3mediated signaling induces NF-kB activation and proinflammatory cytokine and chemokine secretion in infected cultured hepatoma cells, as well as in primary human hepatocytes [165]. TLR3 polymorphisms have also been associated with CHB and hepatitis B-related HCC [167,168], whereas TLR3 recognition of HCV dsRNA has been linked to the induction of chronic hepatitis and HCC [169]. The lack of a mouse model of HBV infection has limited our understanding of the role of TLR3/ TRIF signaling; however, genetic evidence has provided critical insights.…”
Section: Trif-dependent Antiviral Responsesmentioning
confidence: 99%
“…SNP rs3775291 (1234 C>T) is a nonsynonymous mutation (Leu412Phe) located in the fourth exon and occurs very frequently in HCV carriers who require liver transplantation (6) . In addition, rs3775291 is a risk factor for chronic HBV infection (10) and has been associated with resistance to human immunodefi ciency virus (HIV) infection (11) (12) . Given these reports concerning the influence of the TLR3 gene on infections caused by HCV and HBV, the present study investigated the prevalence of TLR3 SNPs rs5743305 and rs3775291 in hepatitis patients who visited a northern Brazil hospital that is a regional reference for the treatment of hepatic diseases.…”
Section: Toll-like Receptor 3 Gene Polymorphisms Are Not Associated Wmentioning
confidence: 99%